Conscious Parenting: Membangun Kesadaran Kritis Menuju Relasi yang Humanis Berbasis Keluarga - Rohinah, Rohinah (ACIECE, 2016)
Unequal relationships between parents who are considered as being superior while the child is positioned as inferior beings actually become a seedbed of the roots of violence in the family. Children are always considered as the little creatures who do not know anything so all the best decision in the hands of older people with communication space is dominated by one direction and full of instructive. In view of Paulo Freire's critical awareness in developing relations egalitarian anywhere and in education whatsoever including education that exists between parents and children need at least the elements of humanization, education and upbringing facing problems, the space for dialogue, awareness (konsientisasi). Family played by fathers and mothers as partners and primary educator and the first in the world of education would have to be in line with the values of humanist-egalitarian to be desirable in the world of formal education. So that the achievement of critical-humanist generation may be to acknowledge that education played by parents before children enter the world of school. So, parents are expected to have a critical view-humanist and egalitarian parenting, assisting and educating children at home.